2008
DOI: 10.1103/physrevd.78.064006
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes of black holes localized on the Randall-Sundrum 2-brane

Abstract: We investigate conformal scalar, electromagnetic, and massless Dirac quasinormal modes of a brane-localized black hole. The background solution is the four-dimensional black hole on a 2-brane that has been constructed by Emparan, Horowitz, and Myers in the context of a lower dimensional version of the Randall-Sundrum model. The conformally transformed metric admits a Killing tensor, allowing us to obtain separable field equations. We find that the radial equations take the same form as in the four-dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…The quasinormal spectrum of the scalar field was studied for the neutral 136 144 . The standard model fields were also considered in the scenario of the three-brane with finite tension in the six-dimensional bulk 145,146 and on the two-brane in the four-dimensional version of the RandallSundrum model 147 . In higher-dimensional space-time one can consider more complicated black hole configurations, which were studied for the particular case of five-dimensional spacetime.…”
Section: Randall-sundrum Modelsmentioning
confidence: 99%
“…The quasinormal spectrum of the scalar field was studied for the neutral 136 144 . The standard model fields were also considered in the scenario of the three-brane with finite tension in the six-dimensional bulk 145,146 and on the two-brane in the four-dimensional version of the RandallSundrum model 147 . In higher-dimensional space-time one can consider more complicated black hole configurations, which were studied for the particular case of five-dimensional spacetime.…”
Section: Randall-sundrum Modelsmentioning
confidence: 99%
“…This solution is beyond the separable ansatz discussed in ref. [27] for conformal wave equations in PD family. Alternatively, the conformal factor can be determined by the relationĝ µν = (C ρστ λ C ρστ λ ) 1/3 g µν [55,62], on the basis of ambi-Kähler structure.…”
Section: Transformations To the Przanowski-tod Metricmentioning
confidence: 99%
“…The CKY tensor in the PD spacetime allows the integrability and the separation of variables only for conformally invariant field equations. See e.g [27].…”
mentioning
confidence: 99%
“…Ref. 144) found linearized equations for conformal scalar, Maxwell and massless Dirac fields on this background become separable. Using this property, they studied quasinormal modes for those fields, and found that their radial part coincides with that for four-dimensional Schwarzschild black hole while angular part is modulated due to existence of the brane.…”
Section: Exact Solutions In Lower-dimensional Modelmentioning
confidence: 99%